2018
DOI: 10.1002/aoc.4289
|View full text |Cite
|
Sign up to set email alerts
|

Metal complexes of novel Schiff base derived from iron sandwiched organometallic and 4‐nitro‐1,2‐phenylenediamine: Synthesis, characterization, DFT studies, antimicrobial activities and molecular docking

Abstract: The condensation of 2-acetylferrocene with 4-nitro-1,2-phenylenediamine in a 1:1 molar ratio, resulting in formation of a novel bi-dentate organometallic Schiff base ligand (L), (2-(1-((2-amino-5-nitrophenyl)imino)ethyl)cyclopenta-2,4-dien-1-yl)(cyclopenta-2,4-dien-1-yl)iron. Also, its Cr(III), Mn(II), Fe(III), Co(II), Ni(II), Cu(II), Zn(II) and Cd(II) complexes have been synthesized. The stoichiometric ratios of the prepared compounds were estimated using elemental analysis (C, H, N, M), molar conductivity, F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 50 publications
(18 citation statements)
references
References 61 publications
1
17
0
Order By: Relevance
“…These observations suggest that the prepared vanadium mixed metal complexes had similar activity compared to our reported work earlier on vanadium complexes with triazole moiety [18,19]. It was reported that the biological activity of the used co-Ligands (L 2 , L 3 , and L 4 ) were moderate [56][57][58]. In our work it was observed the complexes with the co-ligand (L 4 ) containing thiol group showed better activity than the other complexes.…”
Section: Antimicrobial Testssupporting
confidence: 84%
“…These observations suggest that the prepared vanadium mixed metal complexes had similar activity compared to our reported work earlier on vanadium complexes with triazole moiety [18,19]. It was reported that the biological activity of the used co-Ligands (L 2 , L 3 , and L 4 ) were moderate [56][57][58]. In our work it was observed the complexes with the co-ligand (L 4 ) containing thiol group showed better activity than the other complexes.…”
Section: Antimicrobial Testssupporting
confidence: 84%
“…In general, metal complexes were found to be more toxic than ligand 8 and showed greater activity than neomycin and the naturally occurring fungicide cycloheximide. Several other chromium metal complexes have been recently tested for their antimicrobial efficacy but were not found to be active [41][42][43][44][45].…”
Section: Introductionmentioning
confidence: 99%
“…When we analyzed the out of 8 predicted binding conformations of ligand, Cr(III), Mn(II), Fe(III), Co(II), Ni(II), Cu(II), and Cd(II) with 6Y84 docking, the best confirmations exhibited that the free energies of binding (Δ G ) were − 6.0, − 7.6, − 10.1, − 8.5, − 5.9, − 7.7, − 4.6, and − 6.1 kcal/mol, respectively. All Schiff base complexes are binding through H-donor except ligand is binding by H-acceptor with 3.07, 3.03, 2.99, 2.98, 3.06, 302, 2.95, and 3.07 A° distances, respectively [ 38 , 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%